Rolipram, a Selective Phosphodiesterase 4 Inhibitor, Ameliorates Mechanical Hyperalgesia in a Rat Model of Chemotherapy-Induced Neuropathic Pain through Inhibition of Inflammatory Cytokines in the Dorsal Root Ganglion - Kim, Hee Kee; Hwang, Seon-Hee; Oh, Elizabeth; Abdi, Salahadin (Frontiers in Pharmacology, 2017)
Chemotherapy-induced neuropathic pain is a significant side effect of chemotherapeutic agents and is the most common reason for stopping chemotherapy. The aim of the present study was to find the major site and mechanisms of action by which rolipram, a selective phosphodiesterase-4 inhibitor, alleviates paclitaxel-induced neuropathic pain. Chemotherapy-induced neuropathic pain was induced in adult male Sprague-Dawley rats by intraperitoneal injection of paclitaxel on four alternate days. Rolipram was administered systemically or locally into the lumbar spinal cord, L5 dorsal root ganglion, sciatic nerve, or skin nerve terminal. The mechanical threshold, the protein level of several inflammatory cytokines, and the cellular locations of phosphodiesterase-4 and interleukin-1β in the dorsal root ganglion were measured by using behavioral testing, Western blotting, and immunohistochemistry, respectively. The local administration (0.03-mg) of rolipram in the L5 dorsal root ganglion ameliorated paclitaxel-induced pain behavior more effectively than did local administration in the other sites. Paclitaxel significantly increased the expression of inflammatory cytokines including tumor necrosis factor-α (2.2 times) and interleukin-1β (2.7 times) in the lumbar dorsal root ganglion, and rolipram significantly decreased it. In addition, phosphodiesterase-4 and interleukin-1β were expressed in the dorsal root ganglion neurons and satellite cells and paclitaxel significantly increased the intensity of interleukin-1β (2 times) and rolipram significantly decreased it. These results suggest that the major site of action of rolipram on paclitaxel-induced neuropathic pain in rats was the dorsal root ganglion. Rolipram decreased the expression of inflammatory cytokines in the dorsal root ganglion. Thus, phosphodiesterase-4 inhibitors may ameliorate chemotherapy-induced neuropathic pain by decreasing expression of inflammatory cytokines in the dorsal root ganglion.